Transcriptomic and Lipidomic Profiles in Nasal Polyps of Glucocorticoid Responders and Non-Responders: Before and After Treatment - Zhu, Zhenzhen; Wang, Weiqing; Zha, Yang; Wang, Xiaowei; Wang, Lei; Han, Jinbo; Zhang, Jianmin; Lv, Wei (Frontiers in Pharmacology, 2022)
Background: The pathogenesis of chronic rhinosinusitis with nasal polyps (CRSwNP) and mechanisms underlying different responses to systemic glucocorticoids (GC) remain unclear. The major aim of this study was to explore the transcriptomic and oxidative lipidomic signatures and the effects of GC in patients with different clinical responses. Methods: Nasal polyp biopsies were obtained before and after 14-day oral GC treatment from 16 patients with CRSwNP, and normal nasal mucosa specimens were collected from 12 control subjects. RNA sequencing and oxidative lipidomics were performed, and differential gene expression analysis was conducted in the Responder and Non-responder groups at baseline and after treatment. Results: In the Responder group, GC significantly improved clinical symptoms and reduced tissue eosinophil infiltration. Meanwhile, GC led to a pronounced transcriptomic reversion with robust suppression of inflammatory responses and abnormal metabolism of extracellular matrix, as well as restoration of cilia function. However, non-responders were mainly characterized by epithelial hyperplasia and keratinization, with much less transcriptomic improvement after GC treatment. Higher expression of type 2 inflammatory molecules (CCL13, IGHE, CCL18, CCL23, CCR3, and CLC) with lower levels of LACRT, PPDPFL, DES, C6, MUC5B, and SCGB3A1 were related to a stronger clinical response to GC. Besides decreased prostaglandins and increased leukotrienes, increased dysregulation in other oxylipid mediators derived from polyunsaturated fatty acids was determined in nasal polyps, which was ameliorated by GC treatment. Conclusions: Systemic GC exert anti-inflammatory effects, improve tissue remodeling, restore cilia function, and ameliorate dysregulation of oxylipid mediator pathway in CRSwNP. GC-responders exhibited different transcriptomic signatures from non-responders.